Biomass-Derived Surface Engineering of AISI 1020 Steel for Electromedical Applications - Robittah, Ahmad; Akbar Hariyono, Muhammad; Sabitah, A'yan; Achmadi Achmadi; Kusuma Wardani, Ika (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
This study investigates biomass-derived surface engineering of AISI 1020 steel for electromedical applications using galam wood charcoal and chicken bone waste as carburizing media. Surface modification is required to improve the mechanical performance of low-carbon steel, particularly in applications that demand high wear resistance and long-term durability. A pack carburizing approach was applied using various ratios of biomass-derived media at a treatment temperature of 800 °C for 2 hours. Chemical composition was analyzed using Optical Emission Spectroscopy (OES), surface hardness was evaluated using Micro Vickers hardness testing, and microstructural characteristics were observed using optical microscopy. The results show a significant increase in surface carbon content with increasing fractions of chicken bone powder, indicating its effectiveness as a carbon donor and diffusion promoter. The surface hardness increased from approximately 150 HV in the untreated condition to a maximum of about 860 HV in the treated specimen. Microstructural observations revealed the formation of a distinct carburized layer with increasing thickness and uniformity, consistent with enhanced carbon diffusion and surface strengthening. These findings demonstrate that biomass-derived surface engineering provides an effective and sustainable approach for improving the surface properties of low-carbon steel. The proposed method offers strong potential for environmentally friendly manufacturing of durable and reliable electromedical components.